Contrasting Risk Profile in Idiopathic Inflammatory Myopathy (IIM) Patients with Cancer Before and After IIM Diagnosis - Yan Ki Iris Tang; Lucas Luk; Dennis Chan; Billy Lai; Roy Ho; Vivian Tang; Patrick Lee; Ho So (Journal of Clinical Rheumatology and Immunology)
Background: Patients with adult-onset idiopathic inflammatory myopathy (IIM) were at risk of cancer. While the recently published international guideline on cancer screening suggested cancer risk stratification in patients with newly diagnosed IIM, the difference in clinical and serological risk profile among patients with cancer diagnosed before and after IIM diagnosis remained uncertain. Methods: MyoHK was a longitudinal observational cohort that collected data from patients with rheumatologist diagnosis of IIM from 8 rheumatology centres in Hong Kong. Data were reviewed from 2004-2023 for this study. Patients with unavailable myositis specific antibody (MSA) were excluded from analysis. Occurrence of cancer 3 years before to 3 years after the diagnosis of IIM were documented. Patients with active cancer 3 years before diagnosis of IIM were classified to “Prior cancer” group and patients with cancer diagnosed at or within 3 years after IIM diagnosis were classified to “subsequent cancer” group. Patients were stratified to high, intermediate and standard cancer risks. Risk profile between the “prior cancer” and “subsequent cancer” groups were compared. Results: 501 patients were included in analysis. 82 patients had cancer within 3 years, in which 21 patients (25.6%) had cancer within 3 years preceding IIM diagnosis and 61 patients (74.4%) developed cancer at or within 3 years after IIM diagnosis. Nasopharyngeal, lung and breast cancers accounted for the top 3 cancers in both groups. In the “Prior cancer” group, patients were more likely to be female (85.7% vs 55.7%, p = 0.014) and were MSA-negative (33.3% vs 9.8%, p = 0.011). No patient in the “Prior cancer” group developed interstitial lung disease (0% vs 18.0%, p = 0.037) or fulfilled criteria for anti-synthetase syndrome (0% vs 13.1%, p = 0.062). Anti-TIF1g antibody was the most identified MSA in the two groups (42.9% vs 54.1%, p = 374). Myositis-associated-antibody (14.3% vs 42.6%, p = 0.019) and anti-Ro52 antibody (14.3% vs 37.7%, p = 0.047) were more common in the “subsequent cancer” group. In the overall cohort, 228 (45.5%), 246 (49.1%) and 27 (5.4%) of IIM patients were stratified into high, intermediate and standard cancer risk. Two-thirds of the “Prior cancer” group were stratified into high-risk while the remaining one-third being intermediate-risk, compared to 73.8% (p = 0.532) and 26.2% (p = 0.532) in the “subsequent cancer” group. Mortality between the two groups were comparable (38.1% vs 42.6%, p = 0.716). Conclusion: Compared to IIM patients with cancer detected at or after IIM diagnosis, patients with prior cancer were more likely to be female, negative for MSA and absence for ILD.